Respuestas sobre Ia contaminacion de los alimentos en el hogar, comparacion entre madres o cuidadoras de Peru y Costa Rica - Lozada Urbano, Michelle (2015)
Objective: To compare the knowledge of mothers on food contamination in the home between the towns of Peru and Costa Rica. Methods: It was conducted in a rural area of Peru (San Pablo and Huascar) in San Juan de Lurigancho in Lima, and Costa Rica (San Vicente of Three Rivers). The questions were part of a scale that was validated on an expert opinion. It was developed to measure three components or domains.After validation,the instrument was applied in Costa Rica with a group of mothers or caregivers with children under five. The application was developed in Peru in a population with similar characteristics. Results:The sample consisted of 50 caregivers in Costa Rica and 194 in Peru. There is no significant difference in the domains of contamination utensils at home (p=O.750>0.05) and knowledge of child illness (p=0.060>0.05). Knowledge of agents of contamination was highly significant (p=0.000<0.01). In general there is enough evidence to say that knowledge of food contamination in the home are different in mothers of Peru and Costa Rica, (p=0.013 <0.05). Conclusions: No significant differences on pollution and disease. There is highly significant difference in knowledge about pollutants. Overall knowledge of food contamination in the home were higher in mothers or caretakers of Peru.The scale can contribute to the planning of interventions in the aspect of pollution in the home.